A detailed investigation of rare earth lanthanum substitution effects on the structural, morphological, vibrational, optical, dielectric and magnetic properties of Co-Zn spinel ferrites - Hameed, Anam; Asghar, Ali; Shabbir, Saqib; Ahmed, Ishfaq; Tareen, Ayesha Khan; Khan, Karim; Hussain, Gulzar; Awaji, Majed Yousef; Anwar, Hafeez (Frontiers in Chemistry, 2024)
In this work, Co0.5Zn0.5LaxFe2-xO4 (0.00 ≤ x ≤ 0.10) spinel ferrites were synthesized using the sol-gel auto-combustion method. X-ray diffraction (XRD) analysis and Rietveld refinement confirmed the presence of a cubic spinel structure. The crystallite size was estimated to be between 17.5 nm to 26.5 nm using Scherrer's method and 31.27 nm to 54.52 nm using the Williamson-Hall (W-H) method. Lattice constants determined from XRD and Rietveld refinement ranged from (8.440 to 8.433 Å and 8.442 to 8.431 Å), respectively. Scanning electron microscopy (SEM) revealed a non-uniform distribution of morphology with a decrease in particle size. The bandgap values decreased from 2.0 eV to 1.68 eV with increasing rare earth (La 3+ ) doping concentration. Fourier-transform infrared (FT-IR) spectroscopy confirmed the presence of functional groups and M-O vibrations. The dielectric constant and dielectric loss exhibited similar behavior across all samples. The maximum tan δ value obtained at lower frequencies. Regarding magnetic behavior, there was a decrease in magnetization from 55.84 emu/g to 22.08 emu/g and an increase in coercivity from 25.63 Oe to 33.88 Oe with higher doping concentrations. Based on these results, these materials exhibit promising properties for applications in microwave and energy storage devices.